PENERAPAN PROBLEM SOLVING DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA KELAS VII SMP N 1 BANGUNTAPAN - Hanan Prasetya; A. A Sujadi (Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this research is to improve the activity and mathematics achievement of students of class VII with learning methods of problem solving in SMP N 1 Banguntapan. Techniques of data collection in this study was done by observation, documentation, and testing. Test instrument used to test the test item, whereas the observation sheet used to determine the level of involvement of the student. Data analysis techniques for observation sheet was conducted to determine student activity, whereas for mathematics achievement tests done by calculating the average value of the class. The results showed that after the application of the learning methods of problem solving, activity and learning mathematics achievement increased. It can be shown an increase in the average yield percentage of student activity sheets based on the observation student activity first cycle 58.02%, 75% for the second cycle. While the average value of student mathematics achievement increased from an average initial value of 64,34 to 71,99 in the first cycle and second cycle being 80,83. It is expected that schools can apply the learning method.